2010
DOI: 10.1111/j.1365-2672.2010.04746.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of surface protective antigen (spa) types in Erysipelothrix reference strains and diagnostic samples by spa multiplex real-time and conventional PCR assays

Abstract: Aim:  To develop spa multiplex real‐time and conventional PCR assays to detect and differentiate between spaA, spaB and spaC genes within Erysipelothrix spp. Methods and Results:  For evaluation of the assays, 28 Erysipelothrix spp. reference strains, 25 tissues from pigs inoculated with reference strains of serotypes 1, 2, 5, 10 or 18, and 15 diagnostic samples were used. SpaA was found to be present in Erysipelothrix rhusiopathiae serotypes 1a, 1b, 2, 5, 9, 12, 15, 16, 17, 23 and N; spaB was detected in E. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…references strains banked several decades ago, which include spaA, spaB1, spaB2, and spaC. 8,14,20 A cross protection study reported complete protection with homologous spa but only partial protection was observed with heterologous spa strains. 20 Recently, it was determined that a certain spa type is not confined to a specific serotype.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…references strains banked several decades ago, which include spaA, spaB1, spaB2, and spaC. 8,14,20 A cross protection study reported complete protection with homologous spa but only partial protection was observed with heterologous spa strains. 20 Recently, it was determined that a certain spa type is not confined to a specific serotype.…”
mentioning
confidence: 99%
“…14 The isolation results of 70 condemned cases collected at the regional abattoir are summarized in Table 1. Of 70 cases examined, 84.3% (59/70) were found to be culture positive for Erysipelothrix spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SpaA protein was identified in E. rhusiopathiae serotypes 1a, 1b, 2,5,8,9,12,15,16,17, and N, the SpaB protein was identified in E. rhusiopathiae serotypes 4, 6, 11, 19, and 21, and the SpaC protein was identified only in serotype 18 (29). Additional work further differentiated SpaB into subtypes SpaB1 (serotypes 4,6,8,19,21) and SpaB2 (serotype 11) (21).…”
mentioning
confidence: 91%
“…have been isolated from domestic and wild species of both birds and mammals and have been identified as the causative agent of the clinical disease known as "erysipelas" in animals and "erysipeloid" in humans (2). The genus Erysipelothrix consists of four species and 25 associated serotypes: E. rhusiopathiae (serotypes 1a, 1b, 2, 4, 5,6,8,9,11,12,15,16,17,19,21, N), E. tonsillarum (serotypes 3,7,10,14,20,22,23), Erysipelothrix sp. strain 1 (serotype 13), and Erysipelothrix sp.…”
mentioning
confidence: 99%